Tumor suppressor menin is required for subunit-specific nAChR α5 transcription and nAChR-dependent presynaptic facilitation in cultured mouse hippocampal neurons - Angela M. Getz (Nature Portfolio, 2017)
Abstract In the central nervous system (CNS), cholinergic transmission induces synaptic plasticity that is required for learning and memory. However, our understanding of the development and maintenance of cholinergic circuits is limited, as the factors regulating the expression and clustering of neuronal nicotinic acetylcholine receptors (nAChRs) remain poorly defined. Recent studies from our group have implicated calpain-dependent proteolytic fragments of menin, the product of the MEN1 tumor suppressor gene, in coordinating the transcription and synaptic clustering of nAChRs in invertebrate central neurons. Here, we sought to determine whether an analogous cholinergic mechanism underlies menin’s synaptogenic function in the vertebrate CNS. Our data from mouse primary hippocampal cultures demonstrate that menin and its calpain-dependent C-terminal fragment (C-menin) regulate the subunit-specific transcription and synaptic clustering of neuronal nAChRs, respectively. MEN1 knockdown decreased nAChR α5 subunit expression, the clustering of α7 subunit-containing nAChRs at glutamatergic presynaptic terminals, and nicotine-induced presynaptic facilitation. Moreover, the number and function of glutamatergic synapses was unaffected by MEN1 knockdown, indicating that the synaptogenic actions of menin are specific to cholinergic regulation. Taken together, our results suggest that the influence of menin on synapse formation and synaptic plasticity occur via modulation of nAChR channel subunit composition and functional clustering.